2010
DOI: 10.1002/ana.21918
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar morphology in Tourette syndrome and obsessive‐compulsive disorder

Abstract: Objective Neuroanatomical and functional imaging studies have identified the cerebellum as an integral component of motor and language control. Few studies, however, have investigated the role of the cerebellum in Tourette syndrome (TS), a condition defined by the presence of semi-involuntary movements and sounds. Methods Magnetic resonance imaging was conducted in 163 persons with TS and 147 control participants. Multivariate linear regression models were used to explore effects on cerebellar surface morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 38 publications
6
67
0
1
Order By: Relevance
“…46 One study suggested that decreased regional volumes of cerebellar hemispheres were correlated with increased tic severity. 33 In an MRS study, it was shown that the GABA concentration in SM1 correlated negatively with motor tic severity. 53 Amphetamineinduced dopamin release in the ventral striatum was related to increased tic severity in one PET study, 61 while another PET study did not find any correlations between the TS-related metabolic covariance pattern (with increased activity bilaterally in premotor cortex and cerebellum, associated with relative reductions in striatum and orbitofrontal cortices) and severity of tics.…”
Section: Neuroimaging and Severity Of Ticsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 One study suggested that decreased regional volumes of cerebellar hemispheres were correlated with increased tic severity. 33 In an MRS study, it was shown that the GABA concentration in SM1 correlated negatively with motor tic severity. 53 Amphetamineinduced dopamin release in the ventral striatum was related to increased tic severity in one PET study, 61 while another PET study did not find any correlations between the TS-related metabolic covariance pattern (with increased activity bilaterally in premotor cortex and cerebellum, associated with relative reductions in striatum and orbitofrontal cortices) and severity of tics.…”
Section: Neuroimaging and Severity Of Ticsmentioning
confidence: 99%
“…[30][31][32][33] Tobe et al 33 found decreased regional volumes of the cerebellar hemispheres during a finger-tapping test in patients with TS. The authors hypothesize that the cerebellum might be involved in the pathogenesis of TS.…”
Section: Functional Correlates Of Voluntary Motor Executionmentioning
confidence: 99%
“…Expanded perivascular spaces in the midbrain, usually considered a benign incidental finding on MRI, have also been correlated with stereotyped behaviors (Dávila et al, 2010). Disruption of corticocerebellar regulatory loops has been postulated based on MRI findings of reduced volumes of the cerebellum, primarily gray matter in crus I and lobules VI, VIIB, and VIIIA (Tobe et al, 2010). Last, altered MRI volumes of the hippocampus and amygdala and DTI diffusion indices (Neuner et al, 2011) has led to suggestions of direct limbic involvement in TS.…”
Section: Other Brain Regionsmentioning
confidence: 99%
“…Assessing the effects of aging on brain structure in OCD is important, since age-by-disorder interactions may provide leads as to whether changes in brain structure are related to developing the disorder (present in young patients) or are the result of persistent OCD symptoms, compensatory processes, or treatment effects (present in older patients). Additionally, heterogeneity in clinical characteristics such as OCD illness severity (2), illness onset time or duration, medication exposure (12), comorbidity (13,14), and symptom dimensions (8, 9) may affect regional brain volume. In meta-analyses, only group-level demographic and clinical information is available, so accounting for effects of participant-level variability is problematic.…”
mentioning
confidence: 99%